(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
Abstract Nigerian urban environments are characterized by uncontrolled organic and consciously created urban settlements driven by a host of factors. This study used geo-informatic technology to assess the anomalies in the Master Plan of Idah town between 2005 and 2015. The Master Plan of Idah town and high resolution IKONOS images were acquired to provide data for the study while geo-informatic technology was use in the data analysis. The results show that in 2005 residential land use exceeded the expected area in the Master Plan by 1,474,270.6 m2, commercial land use is not accordingly developed having an area of 3,290 m2 encroached upon, that of industrial is encroached upon by 569,766.8 m2, educational is encroached upon by 769,766.8 m2, recreational is encroached upon by 1,521 m2, health is encroached upon by 62,802 m2, religious is encroached upon by 8,026 m2 while government and civic land is encroached upon by 9,265 m2, and transport is encroached upon by 50,333 m2. The study further revealed that the anomalies in the urban Master Plan of Idah town advanced in 2015 with the residential land use exceeded the expected land area designated for it in 2005 by 8,142,704.7 m2 while other land uses that were not fully developed were also encroached upon. Despite the detailed master plan was prepared for Idah town covering the period 1974 to 2005 the implementation is absolutely void. The study recommended that, the Master Plan should be urgently renew to avoid further land use development resulting in more anomalies.